The employment contract in Ecuador: a path to job insecurity - León Fernández, José Alejandro (2020)
When someone goes to a soccer stadium, he always has in his mind a capable, famous and wealthy person who can do everything with an environment of great quality of life, an easy career, but this is only a fiction and the exception of very few with very good luck. If we make an intrinsic review of the principles that govern Labor Law, we review that the principle of equality proposed as a universal fundamental principle and as a «sectorial principle» of Labor Law, has been thought for certain labor sectors, but has not been dedicated as a factor. risk for the professional athlete and especially the footballer, who has not seen them as a weak party, assimilating it, that based on this Law all professional footballers are protected when in reality we review and feel that only elite groups or more specifically, 10% of the professional soccer population worldwide enjoys all the benefits provided by Labor Law, leaving half the enjoyment of all the rights in favor of all this immense labor branch, leading them or inducing them to an existing job insecurity still in the xxi century.